2009
DOI: 10.1345/aph.1m278
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Exposure to Topical Tacrolimus or Pimecrolimus and Cancers

Abstract: Exposure to topical tacrolimus or pimecrolimus was not associated with an increase in the overall cancer rate. Use of topical tacrolimus may be associated with an increased risk of T-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 12 publications
2
84
0
4
Order By: Relevance
“…9 Another report suggested that topical tacrolimus increased the risk of T-cell lymphoma. 10 However, many large-scale analyses have indicated that topical tacrolimus does not increase the risk of malignant lymphoma. [11][12][13][14][15] In addition, topical tacrolimus was effective for the treatment of cutaneous T-cell lymphoma in one case 16 and in the treatment of cutaneous lesions of angioimmunoblastic T-cell lymphoma in another case.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another report suggested that topical tacrolimus increased the risk of T-cell lymphoma. 10 However, many large-scale analyses have indicated that topical tacrolimus does not increase the risk of malignant lymphoma. [11][12][13][14][15] In addition, topical tacrolimus was effective for the treatment of cutaneous T-cell lymphoma in one case 16 and in the treatment of cutaneous lesions of angioimmunoblastic T-cell lymphoma in another case.…”
Section: Discussionmentioning
confidence: 99%
“…An overrepresentation of patients with CTLC in study by Hui et al refers to possible initial misdiagnosis of CTLC as atopic dermatitis and needs to be further substantiated. The risk of TCL associated with use of pimecrolimus cream was insignificantly increased (RR 2.32, 95% CI, 0.89 -6.07) (23,43). A cohort study by Schneeweiss et al reported no significant association between lymphoma and both TCIs (tacrolimus; RR 1.36, 95% CI, 0.47 -3.98, pimecrolimus: RR 1.63, 95% CI, 0.75 -3.54) (24).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the overlapping clinical presentations, early forms of cutaneous T-cell lymphoma (CTCL) might have been initially misdiagnosed for severe AD. Such misdiagnosis probably occurred in the study reported by Hui et al with an overrepresentation of CTLC among tacrolimus users (23). In the meta-analysis by Legendre et al which included two case control studies by Arellano et al (21,22), statistically significant association between highly potent topical corticosteroids and increased risk of lymphoma with an overall OR for lymphoma of 1.73 (95% CI, 1.52 -1.97) might have also been confounded by severity of AD due to low exposure to TCSs before lymphoma occurrence (< 6 months to 12 months).…”
Section: Atopic Dermatitis Per Se and Increased Risk For Lymphomamentioning
confidence: 93%
See 1 more Smart Citation
“…Hui et al and Arana et al identified an increased risk of T-cell lymphoma with TL use. 3,4) In contrast, other studies revealed no significant differences between TL use and non-use with regard to an increased risk of lymphoma. 5,6) Due to short durations and potential study biases in these reports, results have been controversial.…”
mentioning
confidence: 92%